Implementation of Bound Morpheme Through A Text to The Students of HKBP Nommensen Pematangsiantar University - Munthe, Melda Veby Ristella (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Words are composed of morphemes. The notion that morphemes are words is not necessarily true. While some single morphemes can function as words, some words have two or more morphemes. Furthermore, it is wrong to consider morphemes to be syllables. In contrast, many words only have one syllable and two morphemes; examples are "cats," "runs," and "barked." Morpheme can be classified as either Free or Bound Morpheme. It applies the Bound Morpheme's restriction, which included eight inflectional affixes. The goal is to determine how pupils use bound morphemes. This study's research tool was acquired through testing. Knowing the sort of error and where it happens helps with testing. The procedures for data analysis were applied by the data analysis methodologies. Counted the Bound Morpheme first. Second, they were divided into groups. Thirdly, the number of frequently occurring terms was counted. Fourthly, determined which word should be chosen and which should not be. Then, based on the total number of words with the ratings Excellent, Good, Fair, and Poor, percentages were calculated. Meanwhile, based on the results of the The student’s ability in implementing the Inflectional Affixes is 38% as a very good category, 25% as a good category, 25% as a fair category, and 12% as a low category in implementing the Inflectional Affixes of Bound Morpheme on the text.